2009
DOI: 10.1063/1.3271177
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile resistive switching in graphene oxide thin films

Abstract: Reliable and reproducible resistive switching behaviors were observed in graphene oxide (GO) thin films prepared by the vacuum filtration method. The Cu/GO/Pt structure showed an on/off ratio of about 20, a retention time of more than 104 s, and switching threshold voltages of less than 1 V. The switching effect could be understood by considering the desorption/absorption of oxygen-related groups on the GO sheets as well as the diffusion of the top electrodes. Our experiments indicate that GO is potentially us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
181
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(189 citation statements)
references
References 37 publications
4
181
3
1
Order By: Relevance
“…Novel devices have been reported that combine the superior electronic properties of graphene with other chemical and mechanical phenomena, such as resistive switching and electromechanical memories. [20][21][22] The mechanism of observed resistive switching in some graphene-based devices remained unclear. Graphene oxide (GO) is an insulator with a large effective band gap and band structure that depends on the stoichiometry.…”
Section: Reversible Electrical Reduction and Oxidation Of Graphene Oxidementioning
confidence: 99%
“…Novel devices have been reported that combine the superior electronic properties of graphene with other chemical and mechanical phenomena, such as resistive switching and electromechanical memories. [20][21][22] The mechanism of observed resistive switching in some graphene-based devices remained unclear. Graphene oxide (GO) is an insulator with a large effective band gap and band structure that depends on the stoichiometry.…”
Section: Reversible Electrical Reduction and Oxidation Of Graphene Oxidementioning
confidence: 99%
“…Carbon-based materials, including amorphous carbon (a-C) [17]- [26], fullerene [27], graphene oxide [28], [29], carbon/ organic composite [30], and carbon nanotube (CNT) [31], have been shown to exhibit resistive switching behavior for nonvolatile memory application. Amorphous carbon is a noncrystalline carbon allotrope in which a long-range crystalline order is not present.…”
mentioning
confidence: 99%
“…24 It all depends on oxygen diffusion and mobility on the surface of the graphene plane. 41 The oxygen diffusivity is determined from the equation:…”
Section: Resultsmentioning
confidence: 99%
“…Their bandstructure and electronic congurations can be easily modulated by changing the chemical functionalities attached to the surface. [24][25][26][27] High quality GO akes are usually prepared by chemical oxidation of natural graphite with exfoliation into individual layers. The chemical properties of these individual layers can be signicantly tuned by oxidation; one can achieve graphene with the complete removal of the carbon-oxygen (C-O) bond.…”
mentioning
confidence: 99%